Seeds of Change: Transforming Agriculture in Odisha's Koraput - Janakiraman, Deepa (CGIAR, 2024)
The Transforming Agrifood Systems in South Asia (TAFSSA) initiative has introduced the innovative Small Farmers Large Field (SFLF) model to address farming challenges in Koraput district, located in southern Odisha, India. In this region, farming is more than just a means of livelihood—it is deeply woven into the cultural fabric of the community. The SFLF approach consolidates fragmented landholdings, promoting collaboration and unity among smallholder farmers to enhance productivity and sustainability.